2009
DOI: 10.1100/tsw.2009.74
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Various Morphologic and Hemodynamic Carotid Plaque Characteristics on Neurological Events Onset and Deaths

Abstract: A group of 72 patients with 111 asymptomatic carotid stenoses (ACS), mean age 65.42 ± 9.21, and a group of 36 patients with 58 symptomatic carotid stenoses (SCS), mean age 67.63 ± 8.79, were analyzed prospectively during a 3-year follow-up period. All patients underwent color duplex scan sonography (CDS), carotid arteriography, computed tomography (CT) scan, and neurological examination. The aim of the study was to analyze the correlation between echo plaque morphology (degree and plaque quality), local hemody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
5
0
3
Order By: Relevance
“…Numerous studies have shown that an increased IMT is an early marker of generalized atherosclerosis [30,31], and an important predictor of coronary and cerebrovascular complications [2,24,32]. Saba and colleagues [33] demonstrated that the thicker common carotid wall is associated with the development of cerebral ischemic events [37]. Clinically evident cardiovascular disease frequently arises as a late manifestation of widespread atherosclerosis, typically after a long subclinical phase beginning at an early age, and manifests as endothelial damage jointly with a gradual thickening of the IMT [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that an increased IMT is an early marker of generalized atherosclerosis [30,31], and an important predictor of coronary and cerebrovascular complications [2,24,32]. Saba and colleagues [33] demonstrated that the thicker common carotid wall is associated with the development of cerebral ischemic events [37]. Clinically evident cardiovascular disease frequently arises as a late manifestation of widespread atherosclerosis, typically after a long subclinical phase beginning at an early age, and manifests as endothelial damage jointly with a gradual thickening of the IMT [24].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that MDCTA can also provide additional information with the CC-CAWT measurements. In most medical centers, CD-US is the first and frequently a sufficient method for evaluation of stenosis degree, type of plaque, and presence of ulceration; it gives enough data to diminish the risk for patients [37]. MDCTA is not recommended as a routine method [3], but in cases where clinically indicated (according to the guidelines accepted in each institution), CAWT should be always quantified by MDCTA [24,38].…”
mentioning
confidence: 99%
“…Furthermore, noncalcified carotid plaques commonly exhibit a higher degree of fibrous cap inflammation, a key process in fibrous cap disruption. Calcification in ATS lesions is relatively common and has been implicated as a risk factor for increased cardiovascular morbidity and mortality (8,9), while Bayturan et al (10) and Hashimoto et al (11) demonstrated that carotid ATS plaque calcification is a structural marker for carotid plaque stability.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have correlated ulceration with symptoms even in plaques causing low-grade stenosis (≤50%) [ 38 ]. Ulceration is more frequently found in symptomatic carotid plaques [ 39 ] and is also associated with the occurrence of new symptoms in asymptomatic patients [ 40 ]. Indeed, multiparametric analysis has confirmed the correlation of ipsilateral TIA or stroke with the presence of carotid ulceration in asymptomatic prospectively observed patients [ 41 ].…”
Section: Clinical Significance Of Ulcerationmentioning
confidence: 99%